Produktivitas Hijauan Makanan Ternak Pada Lahan Perkebunan Kelapa Sawit berbagai Kelompok Umur di PTPN 6 Kabupaten Batanghari Propinsi Jambi - Farizaldi, Farizaldi (Fakultas Peternakan Universitas Jambi, 2011)
This study was conducted to measure forage productivity at Batanghari Distric Palm Oil Plantation(PTPN 6) of different ages( 3,5, and 8 years ) of the palm trees in Province of Jambi. Purposive sampling was the methode of selecting sampling location.Data were subjected to unpaired t test. The results showed that botanical composition of grass and legume was significantly ( P < 0.05 ) different among three different plantation. Carrying capacity in the the 3-year palm oil plantation was not significantly( P > 0.05 ) with that of in the 5-year palm oil plantation but it was sifnificantly( P < 0.05 ) different with the 8-year palm oil plantation Carrying capacity in the 5- year palm oil plantation was significantly( P< 0.05 ) different from that in the 8-year. The dry matter production of grass and legume on the 3-year palm oil plantation was not significantly( P > 0.05 ) different from that on 5-year palm oil plantation but it was significantly( P < 0.05 ) different from that on 8-year plam oil plantation; The dry matter production of grass and legume on 5-year palm oil palantation was significantly( P < 0.05 ) different from that on 8-year palm oil plantation. It could be conclude that the productivity of forage available at the palm oil plantation field looked decreased with the age of the palm oil plantation field.